Hermeneutical concepts of religious experience - Król, Józef (Studia Psychologica: Theoria et praxis, 2003)
The article presents hermeneutical concepts of religious experience. The first section shows Gadamer’s views on hermeneutical approach to experience,  according to which experience is a process, a “movement” of awareness leading to a mindful embrace of something, to a creation of an insight. The second section presents the notion of a religious experience. Particular attention has been paid to the integral structure of a religious experience containing elements of cognitive, intellectual, emotional and evaluative nature. The last part of the article presents a hermeneutical notion of religious experience. It presents the dialogical, historical and symbolic character of religious experience.